Facial Hair Transplantation for Transgender Patients: A Literature Review and Guidelines for Practice. (10th February 2021) - Patel, Viren; Nolan, Ian T; Card, Elizabeth; Morrison, Shane D; Bared, Anthony
Abstract: Background: Facial hair transplantation has become an increasingly popular modality to create a more masculine appearance for transmasculine patients. Objectives: This aim of this study was to review the current literature regarding facial hair transplantation and provide recommendations and best practices for transgender patients. Methods: A comprehensive literature search of the PubMed, MEDLINE, and Embase databases was conducted for studies published through April 2020 for publications discussing facial hair transplant in transmasculine patients, in addition to the nontransgender population. Data extracted include patient demographics, techniques, outcomes, complications, and patient satisfaction. Results: We identified 2 articles discussing facial hair transplantation in transmasculine patients. Due to the paucity of publications describing facial hair transplantation in transmasculine patients, data regarding facial hair transplant from the cisgender population were utilized to augment our review and recommendations. Conclusions: Facial hair transplant is a safe and effective means of promoting a masculine appearance for transgender patients. Nevertheless, facial hair transplantation should be deferred until at least 1 year after the initiation of testosterone therapy to allow surgeons to more accurately identify regions that would benefit the most from transplantation. Additionally, providers should engage patients in discussions about any plans to undergo facial masculinization surgery because this can alter the position of transplanted hairs. Currently, follicular unit extraction from the occipital scalp is the preferred technique, with use of the temporal scalp if additional grafts are needed. Patients should be advised that a secondary grafting procedure may be needed a year after initial transplant to achieve desired density. Level of Evidence: 4: